1987
DOI: 10.1093/oxfordjournals.aje.a114747
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic Model for Interhuman Spread of Monreypox

Abstract: With the eradication of smallpox, systematic routine vaccination with vaccinia has ceased and an increasing proportion of the human population in tropical rain forest areas of central and western Africa lacks vaccinia-derived immunity to monkeypox virus. This raises the question of the ability of monkeypox virus to establish and maintain itself in an unvaccinated population through continuous man-to-man transmission. A computerized stochastic model of Monte Carlo type was constructed to assess this potential r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
70
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(72 citation statements)
references
References 0 publications
1
70
0
Order By: Relevance
“…All observed transmission chains were short, but their results showed that past smallpox vaccination gave strong cross-protective immunity against monkeypox, leading to concern that monkeypox might establish sustained transmission in an unvaccinated population. In a pioneering analysis, Jezek et al [48] extrapolated their findings to show that-if nothing changed except the proportion vaccinated in the population-monkeypox would not establish sustained transmission among humans. A follow-up article re-stated this finding in terms of the basic reproductive number, reporting that R 0 for monkeypox in an unvaccinated population (in rural DRC) was approximately 0.83, less than the threshold value of 1 needed for persistent circulation [23].…”
Section: (D) Revisiting the Critiquesmentioning
confidence: 99%
“…All observed transmission chains were short, but their results showed that past smallpox vaccination gave strong cross-protective immunity against monkeypox, leading to concern that monkeypox might establish sustained transmission in an unvaccinated population. In a pioneering analysis, Jezek et al [48] extrapolated their findings to show that-if nothing changed except the proportion vaccinated in the population-monkeypox would not establish sustained transmission among humans. A follow-up article re-stated this finding in terms of the basic reproductive number, reporting that R 0 for monkeypox in an unvaccinated population (in rural DRC) was approximately 0.83, less than the threshold value of 1 needed for persistent circulation [23].…”
Section: (D) Revisiting the Critiquesmentioning
confidence: 99%
“…However, a WHO-sponsored epidemiological investigation of an upsurge of monkeypox cases during 1996 and 1998 in the Democratic Republic of Congo indicated that secondary transmission (person to person), rather than primary transmission (animal to human), accounted for the majority of those cases. 16,17,56,85,140 Monkeypox in humans is similar to classic variola major and is characterized by exanthema, fever, and respiratory signs. In contrast to smallpox, human monkeypox has a lower case mortality rate (approximately 10%), and there is striking peripheral lymphadenopathy, usually involving cervical and inguinal lymph nodes.…”
Section: Monkeypox In Africamentioning
confidence: 99%
“…This intensive surveillance accounted for 338 of the 404 recognized cases in Africa during this period (13). Epidemiologic data from this program was used to create a stochastic model for spread of monkeypox between humans, which indicated that monkeypox virus was highly unlikely to sustain itself in human populations and, therefore, did not constitute a major public health problem (14,15). This modeling analysis used available information to predict the future of monkeypox dynamics when the population was completely unvaccinated, but did not include statistical uncertainties and could not account for changes in the ecological reservoir and subsequent epidemiology.…”
mentioning
confidence: 99%